PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KABUPATEN TAPANULI TENGAH - Askal Wahid Sihite; Yacub Hutabarat; Zafril Abdi Nasution (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This thesis is the result of research that describes how much influence Organizational Culture and Work Environment have on Employee Performance at the Environmental Service Office of Central Tapanuli Regency. In this study, several tests were carried out to determine the effect. Based on the description of the results of the research on the Influence of Organizational Culture and Work Environment on Employee Performance at the Environmental Office of Central Tapanuli Regency, it can be concluded as follows: Based on the correlation coefficient there is an adequate/moderate and positive relationship of 0.682 between Organizational Culture on Performance and 0.608 between Environment Work Against Performance, based on the Determination coefficient obtained at 0.541, this means that the model's ability to explain variations in Organizational Culture and Work Environment by Performance is 54.1% at the Environmental Service of Central Tapanuli Regency, while the rest is explained by other variables not included in the model by 45.9%, based on Simple Linear Regression the regression equation obtained is Y = 8.896 + 0.488X1 + 0.286X2 which shows employee performance will increase if Organizational Culture increases by a coefficient of 0.488 and Work Environment by 0.286 if at mas ing each independent variable (free) added with one-unit, and Based on the hypothesis test conducted by comparing the value of t count with t table it can be found that organizational culture and work environment variables with t calculated value are greater than t table, namely 4.577 > 2.00247 and 3.051 > 2.00247. And the significance value is 0.000 below α 5% and 0.003 below α 5%. Because t count is greater than t table, each independent variable has a positive or unidirectional influence on employee performance at the Environmental Service Office of Central Tapanuli Regency and the hypothesis proposed is accepted.